Students’ perspectives on a podcast-based assignment exercise, while learning to communicate about infections and vaccines - Ali Al-Rubaie; Pragalathan Apputhurai; Charmaine Lloyd (Microbiology Australia, 2023)
Podcasts are used in educational institutions to complement learning and revision. In this paper, the incorporation of a student-created podcast component into a group assignment on vaccines was evaluated. It was hypothesised that group podcast preparation would enable health-science undergraduate students to improve their health communication and digital literacy skills. Students (n=66) were introduced to the assignment early in semester 2 of 2022, after which they attended regular coursework and training on podcasting software. Students had the opportunity to research, plan, script, curate and record their podcasts, actively engaging in a social constructivist learning approach. The audio conversation was recorded in a mock roleplay setting between health experts and laypersons, both played by students. The content comprised scientific aspects, conflicting opinions and contemporary issues on the vaccine topic, in the context of a lay-audience scenario provided in the assignment. The packaged podcast was graded for soundness of content, roleplaying, ability to engage the listener and creativity. Student perspectives and feedback were collected before and after the assignment through short online surveys comprising open-ended and Likert questions. Pairwise analysis showed improved digital literacy, improved confidence in students’ own communication skills and preference for podcast assignments (P<0.05). Positive comments included the experience of learning about vaccines, use of podcasting software and fun. Though the podcast approach took a longer time to implement, it was an effective means of facilitating group discussion on the topic and offered students a safe space to experiment communication of health and infection topics through podcast technology.